If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -167 + 9x = -1x + 83 Reorder the terms: -167 + 9x = 83 + -1x Solving -167 + 9x = 83 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -167 + 9x + x = 83 + -1x + x Combine like terms: 9x + x = 10x -167 + 10x = 83 + -1x + x Combine like terms: -1x + x = 0 -167 + 10x = 83 + 0 -167 + 10x = 83 Add '167' to each side of the equation. -167 + 167 + 10x = 83 + 167 Combine like terms: -167 + 167 = 0 0 + 10x = 83 + 167 10x = 83 + 167 Combine like terms: 83 + 167 = 250 10x = 250 Divide each side by '10'. x = 25 Simplifying x = 25
| 4x+3+10x= | | 3w+2=23 | | (X+3)(x+12)= | | x+(x+5)+(x+4)=51 | | 3x+27=9x+39 | | 2x+(x-3)=5x-(2x+5) | | x+(x+5)+(x+4)= | | 6b-4b-b=8 | | 2x^2+5x-400=0 | | 5x+3=-2x | | .15x+.5y=112.5 | | 23x+29y=-13 | | 15ab+4ab+7ab= | | 5p-3p=20 | | 3(x+2)=4x-(x-6) | | 10x-7x=18 | | 4z+3(6-z)=-(z-2)+10 | | -3(-8x+8)-2x=4x-16-2 | | 4z+3(6-z)=-(z+2)+10 | | 2(5x)+2(3x)+2x=72 | | 4u+3u=20 | | -3(x-4)=4(x-1)-3 | | 7x-8+13x=3x+2+2x | | 9p+12p-3p= | | -2(f-12)=-2 | | 6x+9-4=11x+12 | | 6p-2p=7 | | 4cos^3x=5cosx | | 2y(4x-6)=24 | | 10x-3=3x+13 | | -6y+9(5y+7)=7-5(1-y) | | 8x-1(6x+6)=8 |